Workshop Penerapan Pendekatan STEAM untuk Meningkatkan Kompetensi Guru PAUD - Sudarti, Sudarti; Fitriani, Fitriani; Hendriani, Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
The STEAM approach has been adapted to the characteristics of PAUD learning, but there are still many teachers who fail to understand, develop and innovate this approach to make it easier for children to use. The goal of STEAM outcomes is for children to acquire the 4C skills, which are the four skills that are very important in modern life in the 21st century. This corresponds to the partner's problem: qualitatively, only a small percentage of teachers understand STEAM concepts but still have difficulty providing instruction to their children. To implement STEAM in PAUD-based learning, both partners need additional knowledge and skills. The training was carried out for two days, the training participants for this activity reached 53 participants. During the activity, two PG PAUD students were assisted. The result of this training is a change in knowledge and understanding of the preparation of teaching modules for the Merdeka Curriculum using the STEAM approach as part of teacher competency to be able to carry out learning practices using the STEAM approach in the Merdeka Curriculum.